Digital Multicultural Learning Media via Google Sites for Civic Education: Media Pembelajaran Digital Multikultural Berbasis Google Sites untuk Pendidikan Pancasila - Hardianto Hardianto; Nursalam Nursalam; Muhajir Muhajir (Academia Open, 2026)
General Background: The integration of interactive digital media is essential in modern elementary education to adapt to globalization and meet the learning needs of digital-native students. Specific Background: Civic Education (PKn) at the elementary school level in Tanrutedong District currently relies on traditional lectures and textbook-based instruction, failing to foster student engagement or internalize multicultural character values. Knowledge Gap: Existing research on digital learning media predominantly emphasizes cognitive outcomes, leaving a significant deficiency in studies that specifically address the affective development of tolerance attitudes within diverse, multicultural classroom environments. Aims: This study aims to develop and test the effectiveness of a multicultural-based digital learning media platform assisted by Google Sites to improve student tolerance and PKn learning outcomes. Results: Utilizing the ADDIE R&D model, the media integrated Bugis-Makassar 3S local wisdom principles (Sipakatau, Sipakalebbi, Sipakainge). Validation results confirmed a very high validity (Gregory’s coefficient = 1.00), and empirical testing revealed a significant N-Gain average of 0.73, signifying high effectiveness in improving both academic achievement and tolerance. Novelty: The study uniquely bridges digital technology with localized Bugis-Makassar cultural values to create a contextually relevant and inclusive educational framework. Implications: This interactive digital platform provides educators with a scalable, practical, and meaningful tool to cultivate democratic character and national unity, suggesting that technology-driven localized pedagogy is vital for character formation in elementary schools. Highlights The Google Sites-based digital media achieved a perfect Gregory validity coefficient of 1.00, demonstrating high expert-approved instructional design quality. Integration of the Bugis-Makassar 3S principles significantly increased student tolerance attitudes through contextual and culturally relevant learning experiences. Quantitative N-Gain analysis confirms high effectiveness in improving learning outcomes compared to conventional teacher-centered instructional methods. Keywords Digital Media; Google Sites; Multicultural Approach; Tolerance Attitude; Civics Learning Outcomes